Love and the dream come true [large type] - Gray, Tammy L. (Gray, Tammy L. State of grace., 2022)
"Four years after getting the biggest break of his life, Cameron Lee's music career has taken a nosedive, leaving him two options: become a sellout or give up on his lifelong dream. He reluctantly returns home for his sister's wedding, hoping to avoid his past and find his love for music again. Single mom Lexie Walters has suffered her fair share of tragedies and setbacks, but she has finally scraped together the money to achieve her dream of going into business with her cousin as an interior designer. When Lexie's life is at an all-time high, she runs into her teenage crush, Cameron Lee. Lost in the emotional turmoil of failure, Cameron is immediately drawn to Lexie and her infectious smile and optimistic spirit. Moreover, he adores her mouthy, no-holds-barred daughter. But fantasies only last so long, and soon Lexie and Cameron must face the real world, the one fraught with heartbreak, disappointment, and questions that sometimes can only be answered by a leap of faith"-- Provided by publisher.